Field study on the analysis of cooling load in PTAR library - Haneefa, Muhammad Ariffadhillah; Hussin, Norasikin; Suhaimi, Muhammad Syihabuddin; Abd Razak, Azli (Universiti Teknologi MARA, Kedah, 2017)
Energy consumption is the biggest issues in commercial sector such as government office, educational building and so on. The library building is important in educational building. The function of the library is to provide the information which supports lifelong learning and continuing education for students. Commonly, the air conditioning is higher consumer energy consumption in commercial sectors. A field study was conducted in library building as known as Perpustakaan Tun Abdul Razak (PTAR UiTMCPP). The objective of this project is to identify factors that contribute to energy usage and to analyse the percentage of energy saving. The set of questionnaires has distributed to 300 respondents and interviews were conducted to find out the level of satisfaction of library conditions. The results show that 63% respondents reported feeling uncomfortable becauseof the higher cooling load. Based on the observation, the resetting cooling load is required follows the ASHRAE Standard 55. The Integrated Environmental Solution <Virtual Environment> (IES <VE>) software is used to identify the percentage of reducing electricity consumption. The IES <VE> software can give a specific data of the building energy consumption. The setting cooling load, 17ºC and resetting 24ºC has been analysed using IES <VE>. The result from IES <VE> is given that energy consumption for cooling is reduced by at least 44.77% per year when the set point temperature changed from 17°C to 24°C. Findings of this field study are useful in air conditioning system with energy savings for PTAR UiTMCPP.